2020
DOI: 10.1038/s41598-020-59683-z
|View full text |Cite
|
Sign up to set email alerts
|

Brushed lubricant-impregnated surfaces (BLIS) for long-lasting high condensation heat transfer

Abstract: Recently, lubricant-impregnated surfaces (LIS) have emerged as a promising condenser surface by facilitating the removal of condensates from the surface. However, LIS has the critical limitation in that lubricant oil is depleted along with the removal of condensates. Such oil depletion is significantly aggravated under high condensation heat transfer. Here we propose a brushed LIS (BLIS) that can allow the application of LIS under high condensation heat transfer indefinitely by overcoming the previous oil depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Similar design of hybrid micro/nanostructured surfaces with wetting contrast can be found in the literature [64,106,107]. The slippery liquid-infused porous surface has been widely studied to promote droplet mobility [5,28,[108][109][110][111][112]. A hydrophilic directional slippery rough surface was recently fabricated to improve droplet nucleation and removal [5].…”
Section: Potential Strategies For Condensation Enhancementmentioning
confidence: 71%
“…Similar design of hybrid micro/nanostructured surfaces with wetting contrast can be found in the literature [64,106,107]. The slippery liquid-infused porous surface has been widely studied to promote droplet mobility [5,28,[108][109][110][111][112]. A hydrophilic directional slippery rough surface was recently fabricated to improve droplet nucleation and removal [5].…”
Section: Potential Strategies For Condensation Enhancementmentioning
confidence: 71%
“…Despite this practical challenge, LIS has found many potential beneficial applications. For LIS, it has been shown that liquid depletion can easily be overcome by periodically refilling the impregnated liquid ( 39 ). Inspired by this approach, we demonstrate the feasibility of refilling these surfaces to increase longevity of the hemiwicking state by leveraging the prefilled reentrant surface’s ability to wick nonwetting liquids.…”
Section: Discussion Of Limitations and Other Designsmentioning
confidence: 99%
“…Again drawing analogies to previous works designing omniphobic surfaces, which explored the effect of design parameters such as geometry and wettability on the stability of metastable wetting states ( 40 , 41 ), we expect the stability of the metastable state to be improved by increasing the reentrant angle and decreasing pitch; however, decreasing the pitch could prevent vacuum-filling given the breakthrough pressure to force nonwetting liquid into the structures would be increased ( SI Appendix , Text S7 ). On the other hand, design aspects such as making the ratio of the channel depth to the pitch too small could reduce the stability of the metastable hemiwicking state ( 39 ).…”
Section: Discussion Of Limitations and Other Designsmentioning
confidence: 99%
“…[29,30] Replenishing the lubricant requires the addition of complex and expensive mechanisms to the system. [31] The majority of past literature on LISs has shown temporary dropwise condensation over short periods of time (<1 day) for condensation of low surface tension liquids such as toluene, octane, ethanol, pentane, and hexane without addressing long term performance concerns. [22,32] Until now, to the best of our knowledge, the only durability test performed with a LIS was on a copper-based LIS showing sustainable condensation of ethanol and hexane for up to ≈7 h whereas longer durability test has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%